Remote Training of Functional Endoscopic Sinus Surgery With Advanced Manufactured 3D Sinus Models and a Telemedicine System - Suzuki, Masanobu; Vyskocil, Erich; Ogi, Kazuhiro; Matoba, Kotaro; Nakamaru, Yuji; Homma, Akihiro; Wormald, Peter J.; Psaltis, Alkis J. (Frontiers in Surgery, 2021)
Objective: Traditionally, cadaveric courses have been an important tool in surgical education for functional endoscopic sinus surgery (FESS). The recent Covid-19 pandemic, however, has had a significant global impact on such courses due to its travel restrictions, social distancing regulations, and infection risk. Here, we report the world-first remote FESS training course between Japan and Australia, utilizing novel 3D-printed sinus models. We examined the feasibility and educational effect of the course conducted entirely remotely with encrypted telemedicine software. Methods: Three otolaryngologists in Hokkaido, Japan, were trained to perform frontal sinus dissections on novel 3D sinus models of increasing difficulty, by 2 rhinologists located in Adelaide, South Australia. The advanced manufactured sinus models were 3D printed from the CT scans of patients with chronic rhinosinusitis. Using Zoom and the Quintree telemedicine platform, the surgeons in Adelaide first lectured the Japanese surgeons on the Building Block Concept for a 3D understanding of the frontal recess. They in real-time directly supervised the surgeons as they planned and then performed the frontal sinus dissections. The Japanese surgeons were asked to complete a questionnaire pertaining to their experience and the time taken to perform the frontal dissection was recorded. The course was streamed to over 200 otolaryngologists worldwide. Results: All dissectors completed 5 frontal sinusotomies. The time to identify the frontal sinus drainage pathway (FSDP) significantly reduced from 1292±672 sec to 321±267 sec (p=0.02), despite an increase in the difficulty of the frontal recess anatomy. Image analysis revealed the volume of FSDP was improved (2.36±0.00 ml to 9.70±1.49 ml, p=0.014). Questionnaires showed the course’s general benefit was 95.47±5.13 in dissectors and 89.24±15.75 in audiences. Conclusion: The combination of telemedicine software, web-conferencing technology, standardized 3D sinus models, and expert supervision, provides excellent training outcomes for surgeons in circumstances when classical surgical workshops cannot be realized.